Outcome of extracorporeal shock wave lithotripsy for renal and upper ureteric stone clearance - Regmi, Prabodh; Adhikari, Baikuntha; Chapagain, Anup; Shah, Chitaranjan; Basnet, Robin Bahadur; Shah, Jay Narayan (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Extracorporeal shockwave lithotripsy (ESWL) is a day care, less invasive procedure not requiring anesthesia for the treatment of renal and ureteric stones. Method: This was a cross sectional study of retrospectively collected data on ESWL during May 2018 to January 2020 at the department of Urology, Bir Hospital, National Academy of Medical Sciences (NAMS), Nepal. The data on ESWL for renal and upper ureteric stone up to the size of 20 mm were included. Stone clearance was defined as stone fragment <4 mm on kidney ureter bladder (KUB) X-ray or ultrasonography (USG) during follow up at 1 - 3 mo. Ethical approval was obtained from NAMS ethical committee. Microsoft Excel was used for descriptive analysis of age, gender, stone size, density, location, hydronephrosis, and clearance. A Chi square test was used for association, and a p-value <0.05 considered statistically significant. Result: Out of 79 cases, overall stone clearance was 48(60.8%), 100% for <10 mm (14/14) and density <500 HU (5/5), and 80% for upper ureteric stone (4/5) and 74.1% for those without hydronephrosis (20/27). Patients in age group of 20-39 y accounted for 48(60.8%), males 52(65.8%), 52(65%) had 10-15 mm stones, 46(58.2%) in pelvis, 48(60.8%) density of 751-1000 HU, and mild hydronephrosis present in 44(55.7%). Conclusion: Stone clearance were highest (100%) for small stone <10 mm size and low density <500 HU. The stone clearance rate decreased as the size, density, and hydronephrosis increased.